ANA Negative Systemic Lupus Erythematosus Leading to CTEPH, TTP-Like Thrombocytopenia, and Skin Ulcers - Khalid Hamid Changal; Fayaz Sofi; Sheikh Shoaib Altaf; Adnan Raina; Ab. Hameed Raina (Case Reports in Rheumatology)
SLE affects almost every organ system, with differing degrees of severity. During its clinical course periods of flares may alternate with periods of remission culminating in disease and therapy related damage. We describe a case of ANA negative SLE with severe thrombocytopenia, cutaneous vasculitis, antiphospholipid antibody syndrome, and pulmonary artery hypertension. As there is no definitive cure for SLE the treatment lies in caring for the individual organ systems involved and simultaneously taking care of the patient as a whole.